Increasing the Upper Mass/charge Limit of a Quadrupole Ion Trap for Ion/Ion Reaction Product Analysis via Waveform Switching - Lee, Kenneth W. (J Am Soc Mass Spectrom, 2019)
Quadrupole ion traps (QITs) are versatile platforms for performing experiments with gas-phase ions due to their abilities to store ions of both polarities and to conduct MS(n) experiments. The QIT is particularly useful as a reaction cell for ion/ion reactions. In the case of an ion/ion reaction experiment in a QIT, multiply-charged reactant ions may initially be of relatively low m/z (e.g., m/z <1000) whereas the product ions can be one or more orders of magnitude higher in m/z (e.g., m/z >100,000). Several factors can limit the m/z range over which an ion/ion reaction experiment can be conducted. These include 1) the efficiency of the detector, 2) the m/z range over which oppositely-charged ions can be mutually stored, and 3) the m/z range over which ions can be mass-selectively ejected into an external detector. High frequency waveforms provide larger m/z trapping ranges for mutual storage of oppositely charged ions whereas low frequency waveforms provide better trapping for very high m/z product ions. Presented here is a method that switches from a high frequency sine-wave prior to and during an ion/ion reaction to a low frequency square-wave to eject low m/z reagent ions and improve confinement of the product ions before mass-selective ejection by scanning the frequency of the square-wave. This approach addresses the third issue, which is the primary limiting factor with QITs operated at high RF frequencies (e.g., > 900 MHz).